SAFETY AND EFFICACY OF ADENO-ASSOCIATED VIRAL VECTOR MEDIATED INTRAUTERINE GENE THERAPY FOLLOWING EARLY- AND LATE-GESTATION INTERVENTION IN A NON-HUMAN PRIMATE MODEL - Citra Nurfarah Zaini Mattar (2019)
2nd International Conference on In Utero Transplantation and Fetal Gene Therapy (iFETIS)